THE POTENTIAL USE OF SSR MARKERS TO SUPPORT THE MORPHOLOGICAL IDENTIFICATION OF INDONESIAN MUNGBEAN VARIETIES - Reflinur Reflinur; Puji Lestari; Suk-Ha Lee (Indonesian Journal of Agricultural Science, 2016)
Mungbean varieties were mainly characterized based on morphological traits. Molecular genetic approach is expected to help the breeder in identification of mungbean varieties in more detail and to protect intellectual property right. This study aimed to identify Indonesian mungbean varieties based on DNA fingerprint profile using a marker set to support morphological characters. A total of 22 Indonesian mungbean accessions were characterized based on 21 morphological traits and 55 simple sequence repeats (SSRs) primers. Of the total 22 mungbean varieties used in the present study, 16 varieties were improved varieties and remaining six varieties were local varieties originated from Java, Nusa Tenggara and Sulawesi collected in GeneBank of ICABIOGRAD. The results showed that the 21 morphological characters were not sufficient to differentiate 22 mungbean varieties, while SSR analysis revealed that eight multi-alleles markers and high polymorphic information content (PIC) values have been successfully selected for varietal identification. The selected markers enabled to differentiate each mungbean variety according to their genetic marker with the lowest distance of 0.125, demonstrating the robustness of the selected marker set as a tool to identify a specific DNA fingerprint profile as a varietal identity (ID). The genetic identity of a variety was shown by digital barcoding which represented a series of alleles produced by corresponding markers. The DNA fingerprint profile of each variety would be beneficial as reference identities of a mungbean variety.